Differences in Body Composition of Football Players of Two Top Football Clubs - Jovan Gardasevic; Dusko Bjelica; Ivan Vasiljevic; Marin Corluka (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2019)
The aim of this research was to determine the differences among the football players of the football club in Bosnia and Herzegovina, CSC Zrinjski Mostar and the football players of the football club in Montenegro FC Sutjeska Niksic, in the anthropometric characteristics and body composition. A sample of 51 subjects was divided into two sub-samples. The first sub-sample of the subjects consisted of 28 football players of CSC Zrinjski Mostar of the average age 24.36±4.14, the champions of the Bosnia and Herzegovina in the season 2016/17, while the other sub-sample consisted of 23 players of FC Sutjeska Niksic of the average age of 21.69±4.30, the winner of the Cup of Montenegro in the season 2016/17. Football players were tested immediately after the end of the competition season 2016/17. Anthropometric characteristics in the body composition were evaluated by a battery of 10 variables: body height, body weight, waist circumference, triceps skinfold, biceps skinfold, skinfold of the back, abdominal skinfold, body mass index, fat percentage and muscle mass. The significance of the differences between the football players of the top two football clubs in the Anthropometric characteristics and variables for assessing body composition was determined by a t-test for independent samples. It was found that the football players of the two mentioned clubs have statistically significant differences by the three variables that estimate the waist circumference, triceps skinfold and skinfold of the back, in a favor of FC Sutjeska Niksic.